The Valuation of Using FDG PET-CT in Detecting Osteoid Osteoma of the Cervical Spine. Issue 2 (March 2015) - Kong, Jinhai; Xiao, Hui; Liu, Tielong; Yan, Wangjun; Qian, Ming; Song, Dian wen; Yang, Xinghai; Wang, Ting; Sun, Zhengwang; Xiao, Jianru
Abstract : Study Design: Osteoid osteomas (OOs) are bone tumors that rarely occur in the cervical spine. The current study is a retrospective analysis on 10 patients who were diagnosed with this rare spinal bone tumor. We have excised OOs of the cervical spine with the use of FDG Positron emission tomography-computed tomography (PET-CT) for preoperative diagnosis. Objective: With the help of the FDG PET-CT, we can confidently remove the nidus of the OOs, while minimize iatrogenic injury of the surrounding normal bone elements, and preserve the stability of the cervical spine. Summary of Background Data: OO of the cervical spine is frequently located at the nerve root adjacent to the vertebral artery, spinal cord. PET-CT is a sensitive tool with applications in the detection of bone lesions, especially in patients with difficult diagnosis or continuing misdiagnosis of tumors. Materials and Methods: Ten patients (8 male and 2 female patients) underwent surgery for tumor removal using PET-CT in our department. Various diagnostic imaging modalities including x-ray, magnetic resonance imaging, CT, bone scintigraphy, and PET-CT were used. PET-CT scan results were measured using standard uptake value. (The size of the cases series was from 4×5 mm to 12×15 mm.) Pain was evaluated using the visual analogue score. Clinical outcome was evaluated immediately postoperatively and at a mean follow-up of 49.8±0.2 months (range, 7–92 mo). Results: All tumors were successfully diagnosed with the use of PET-CT. The average standard uptake value was 2.7±0.1 (range, 2.0–3.4). The nidus of the OO was detected and removed, and the peripheral elements were preserved. The visual analogue score was 8.1±0.1 preoperation, and it significantly decreased to 2.5±0.3 ( P <0.01) postoperation and 0.2±0.1 ( P <0.01) at the final visit. Immediately after surgery, the patients were relieved of their pain symptoms. There was no injury of the vertebral artery, leakage of cerebrospinal fluid, infectious complications, and neurological injury during the procedure. Conclusions: It is valuable of using of PET-CT to diagnose OOs of the cervical vertebra. Subsequently, it is a good way that helps us in efficient removal of the OOs completely.